2007
DOI: 10.1007/s11010-007-9628-x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine inhibits UV-mediated NF-κB activation in A2058 melanoma cells: an ATM-PKCδ-p38 MAPK-dependent mechanism

Abstract: Mammalian ultraviolet (UV) radiation response is a gene induction cascade activated by several transcription factors, including NF-kappaB. Although NF-kappaB is induced by UV radiation, the signal transduction mechanism remains relatively unclear. In the present study, we show that UV-induced NF-kappaB activation is mediated by the activation of Ataxia telangiecia mutated (ATM) and protein kinase C (PKC). We also show that caffeine specifically inhibits UV-mediated NF-kappaB activation, but not TNFalpha-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…Previous study implicated that ATM may be involved in regulating NF-B signaling in UV-treated melanoma cells (38). Using pharmacological and genetic approaches, we demonstrated that ATM is indispensable for NF-B activation by UV treatment, which is conserved among different cell types and between species.…”
Section: Discussionmentioning
confidence: 68%
“…Previous study implicated that ATM may be involved in regulating NF-B signaling in UV-treated melanoma cells (38). Using pharmacological and genetic approaches, we demonstrated that ATM is indispensable for NF-B activation by UV treatment, which is conserved among different cell types and between species.…”
Section: Discussionmentioning
confidence: 68%
“…Caffeine has also been shown to inhibit skin cancer in mice by enhancing UVB-induced apoptosis (35). The experimental doses used in the present study are equivalent to previous in vitro studies (30)(31)(32)(33), although the higher doses are above the physiologic achievable systemic doses. Translating experimental in vitro doses to human in vivo settings frequently requires significant dose adjustments due to pharmacokinetic and pharmacodynamic parameters along with differences in acute in vitro exposure versus cumulative effects following long-term exposure.…”
Section: Discussionmentioning
confidence: 78%
“…The shifted ER proportions are in line with both the clinical and experimental data in the present study. Several studies have described caffeine and caffeic acid as anticarcinogenic agents in various cell culture and in vivo models (30,31). For instance, in hepatocellular carcinoma and epidermal JB6 cells, caffeine attenuated cell growth via induction of G 0 -G 1 cell-cycle arrest (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…26 Similarly, Atm deficiency amplified genotoxicity induced by Phen. 27 Also, inhibition of Atm expression by caffeine, a well-characterized ATM kinase inhibitor, 28 significantly increased APAP hepatotoxicity. 29 Because expression of Atm is largely governed by promoter regulation, 30 and is negatively regulated by displacement of positive transcriptional transactivators with soluble factors (eg, epidermal growth factor or hepatocyte growth factor), 31,32 it should be reasonable to consider whether soluble factors will be relevant in DILI and Atm expression and in improvement of Atm expression after cell therapy.…”
Section: Discussionmentioning
confidence: 99%